Eccentric versus concentric incremental maximal cycling test - Lipski, M.; Abbis, C.; Nosaka, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Eccentric cycling (EC) is less metabolically demanding than concentric cycling (CC) at the same power output (1). To determine eccentric cycling intensity, previous studies have used either a percentage of age-predicted maximum heart rate (2) or maximal power output obtained from a concentric incremental cycling test (1). Maximal power output during eccentric cycling was not assessed in the previous studies, and oxygen consumption (VO2) and heart rate (HR) responses in incremental eccentric exercise have been not investigated. Thus, this study compared changes in VO2 and HR in relation to power output between concentric and eccentric incremental maximal cycling test. Methods: Eleven healthy participants (9 men, 2 women, 33.2 ± 9.2 y) performed two incremental maximal cycling tests on separate days; first on a concentric cycling ergometer (Velotron, Washington USA) then on an eccentric cycling ergometer (Cyclus2 Eccentric Trainer, Germany). Cycling intensity started at 75 W and increased by 25 W every minute until exhaustion. Participants were instructed to cycle above 60 rpm during CC, and to maintain the same cadence as CC during EC. When the target rpm could not be maintained for more than 30 s, the test was terminated. Gas exchange, heart rate and power output were measured continuously during cycling, and compared between EC and CC by a t-test and Cohen`s effect size (dz). Results: Maximal power output was 53% greater (P<0.001; dz=2.11) for EC (438 ± 110 W) than CC (286 ± 55 W). Maximal HR during CC (182 ± 13 bpm) was not different (P>0.05; dz=0.49) from that of EC (176 ± 20 bpm). Peak VO2 was 39% (P<0.001; dz=1.14) greater during CC (43.2 ± 6.8 ml/kg/min) than EC (31.0 ± 5.8 ml/kg/min). Discussion: In spite of the 53% greater power output during EC than CC, peak VO2 was 39% lower for EC than CC, yet maximal HR was similar between EC and CC. Thus, the relationship between VO2 and HR in EC was different from that in CC. It has been shown that the magnitude of increase in adrenaline and noradrenaline is similar between EC and CC (3). It has also been reported that eccentric contractions increase muscle temperature more than concentric contractions (4). These differences may explain why HR responses were similar between EC and CC. In conclusion, the different relationship between maximal power output, VO2, and HR should be considered when prescribing EC. An incremental protocol utilizing eccentric cycling may be more appropriate to determine exercise intensity in future investigations.